Conservation status of the endangered Scaly-sided Merganser Mergus squamatus on the Korean Peninsula - Moores, Nial; Solovyeva, Diana V.; Seung-Kwang, Baek; Su-Young, Lee; Vartanyan, Sergey L. (Wildfowl, 2023)
The Scaly-sided Merganser Mergus squamatus is assessed as an Endangered migratory species globally. Effectively restricted for most of the year to rivers in eastern and northeast Asia, the global population in the wild is estimated at 3,600–4,800 individuals. This century has seen a substantial increase in research and conservation effort in the riverine forests of far eastern Russia and northeastern China, where the species is known to breed, and in eastern China where coordinated surveys have found a large proportion of the global population wintering. Data from geolocating loggers and ground observations confirms that a substantial, though still unknown, number of Scaly-sided Merganser pass through the Korean Peninsula during southward and northward migration. In the Republic of Korea (RO Korea), surveys during southward migration found 144–198 individuals along the Imjin River in 2021, and a total of 215 during one-day surveys of three rivers in November 2022. Based on national winter surveys between 2012 and 2022, probably 5% or more of the population also overwinters in the RO Korea. Status in the Democratic People’s Republic of Korea (DPR Korea) remains less clear. The species is assessed in the RO Korea as Endangered nationally and in the DPR Korea as Threatened. Yet there are no sites on the Korean Peninsula being managed for the conservation of Scaly-sided Mergansers, and every river known to be important for the species is being negatively affected by infrastructural development or disturbance.